Democratic Republic of Sao Tome and Principe : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2016)
This paper discusses the following selected issues related to the Sao Tome and Principe's economy: tourism competitiveness in Sao Tome and Principe-challenges and strategy, macro-financial linkages, private sector development, and challenges of small financial systems. Sao Tome and Principe has experienced significantly faster growth in tourism than most tourism-dependent small states (TDSS). An application of a tourism gravity model shows that Sao Tome and Principe is competitive in compared to TDSS. However, tourism development in this country faces broad challenges both on the micro and micro level. Sao Tome and Principe can do well with venture capital-type financing for micro, small-, and medium-sized enterprises.